2021
DOI: 10.1093/eurheartj/ehab724.1778
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of myocardial fibrosis in hypertrophic cardiomyopathy

Abstract: Background Myocardial fibrosis is a common feature of hypertrophic cardiomyopathy (HCM) but its pathophysiology has yet to be elucidated. Purpose In this study, we used a multiplex approach to examine the genetic regulation of pathways associated with fibrosis in patients undergoing septal myectomy. Methods Myocardial tissue was collected at time of surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has also been suggested that CCN2/CTGF protein could be a biomarker for comparing the severeness of heart failure [ 26 , 27 , 28 ]. Moreover, a recent study comparing patients that underwent septal myectomy due to cardiac hypertrophy to structurally normal hearts that were harvested following non-cardiac-related deaths showed that CCN2/CTGF was significantly upregulated and appeared to be a key mediator of myocardial fibrosis [ 29 ]. This study supports the potential role of CCN2/CTGF as a biomarker of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that CCN2/CTGF protein could be a biomarker for comparing the severeness of heart failure [ 26 , 27 , 28 ]. Moreover, a recent study comparing patients that underwent septal myectomy due to cardiac hypertrophy to structurally normal hearts that were harvested following non-cardiac-related deaths showed that CCN2/CTGF was significantly upregulated and appeared to be a key mediator of myocardial fibrosis [ 29 ]. This study supports the potential role of CCN2/CTGF as a biomarker of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 99%